The risk of breast cancer in BRCA1 and BRCA2 mutation carriers without a first‐degree relative with breast cancer. Issue 5 (25th March 2018) - Metcalfe, K.A.; Lubinski, J.; Gronwald, J.; Huzarski, T.; McCuaig, J.; Lynch, H.T.; Karlan, B.; Foulkes, W.D.; Singer, C.F.; Neuhausen, S.L.; Senter, L.; Eisen, A.; et al.
Abstract : The objective of this study was to estimate the lifetime risk of breast cancer in women with a BRCA1 or BRCA2 mutation with and without at least 1 first‐degree relative with breast cancer. A total of 2835 women with a BRCA1 or BRCA2 mutation were followed. Age‐ and gene‐specific breast cancer rates were calculated. The relative risks of breast cancer for subjects with a family history of breast cancer, compared to no family history were calculated. The mean age at baseline was 41.1 years, and they were followed for a mean of 6.0 years. The estimated penetrance of breast cancer to age 80 years was 60.8% for BRCA1 and 63.1% for BRCA2 . For all BRCA carriers, the penetrance of breast cancer to age 80 for those with no first‐degree relative with breast cancer was 60.4% and 63.3% for those with at least 1 first‐degree relative with breast cancer. The risk of breast cancer for BRCA carriers with no first‐degree relative with breast cancer is substantial, and as a result, clinical management for these women should be the same as those for women with an affected relative. Abstract : Penetrance of breast cancer for BRCA2 carriers by subjects with or without first‐degree relative with breast cancer.